Transcultural Adaptation and Psychometric Properties of the Persian Version of the Nursing Student Competence Scale (NSCS) - Amir Jalali PhD; Fatemeh Chavoshani MSc; Raheleh Rasad MSc; Niloufar Darvishi MSc; Fatemeh Merati Fashi PhD; Mahbod Khodamorovati MD; Khalil Moradi PhD (SAGE Publishing, 2024)
Introduction The competency of a nurse in integrating knowledge, skills, attitudes, and values in various healthcare areas depends on their ability to apply these elements. It is a basic indicator of performance in nursing, and its assessment is a necessity among nursing students. Objective The present study was conducted to determine the psychometric properties of the Persian version of the nursing competence tool for Iranian nursing students in 2023. Methods This is a methodological study in which the Nursing Student Competence Scale (NSCS) was translated into Persian using the forward-backward translation method. A total of 321 nursing students were selected for construct validity by the exploratory factor analysis (EFA) (the first 190 nursing students) and confirmatory factor analysis (CFA) by convenience sampling method. Cronbach's alpha coefficient was used to evaluate the internal consistency, and the test-retest method was used to check the instrument's reliability. Results The results of EFA and CFA confirmed the instrument with six factors and 28 items. The results showed that the fit indices of the model in CFA included (CFI = .91, NNFI = .90, goodness of fit index = .83, root mean square error of approximation = .075, standardized root mean square residual = .047). Pearson's correlation coefficient between items and subscales showed a direct and significant relationship with the main scale. Also, Cronbach's alpha coefficient (0.9) and test-retest (0.88) confirmed the reliability of the Persian version of (NSCS). Conclusion Generally, the Persian version of the NSCS with 28 items and six factors is a valid and reliable scale. This instrument has good internal consistency, validity, and reliability, which can be used to evaluate nursing students' competence in bachelor training.